Improving Student Learning Outcomes Through the Implementation of the Active Knowledge Sharing Learning Model at SMA Negeri 3 Langsa - Ramadani, Antika; Marjanah; Mahyuny, Siska Rita (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2024)
One measure of learning success is seen from the level of understanding and the magnitude of learning outcomes both cognitively, affectively and psychomotorically. The aim of this research is to look at the influence and magnitude of the increase in learning outcomes based on the use of the active knowledge sharing model in class XI students at SMAN 3 Langsa discussing the reproductive system. Pre-experimental with one group pretest and posttest was the design for this research. The research population was all students of class XI Science at SMAN 3 Langsa for the 2022–2023 academic year with 246 students, spread across 7 classes. Class XI IPA 7 was selected as a sample using a simple random sampling procedure. The instrument used is 20 multiple choice test questions which are valid and reliable. Based on the results of research using the active knowledge sharing model, it was found that t count was 23.101 > t table 2.039, so the active knowledge sharing model had an effect on improving learning outcomes. A paired t-test with a significance threshold of 5% was used to determine the results of this data analysis. Furthermore, to see the magnitude of the increase in learning outcomes, an n-gain test was carried out with a value of 0.63 with a percentage increase of 63% in the medium category. So it can be concluded that the application of the active knowledge sharing learning model in the discussion of reproductive systems in class.